ANALISIS PENGGUNAAN MAKNA DIKSI PADA LIRIK LAGU " MALAM TAK BERJUDUL" KARYA MONICA CHRISTIANA - Malika Dhita Shalaika; Windi Kartika Wati; Sukarno (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study analyzes the use and meaning of diction in the lyrics of the song "Malam Tak Berjudul" by Monica Christiana. The song was chosen because it has a wealth of language and deep symbolism, which reflects the emotions and hidden messages behind the words used. This analysis uses a qualitative approach with a descriptive analytical method, focusing on the choice of words (diction) and how they are used to create a certain meaning and atmosphere. The results of the analysis show that Monica Christiana uses diction full of symbolism and emotional connotations to describe the atmosphere of the night full of mystery and loneliness. Words like "night", "untitled", and "sense of loneliness" not only serve as descriptions but also lead the reader to introspective and melancholic feelings. The chosen diction creates a powerful image and influences the listener's interpretation of the song's theme This study concluded that the choice of diction in the lyrics of "Untitled Night" plays an important role in conveying the emotional message of the song. The right choice of words and the use of symbolism are effective in bringing listeners to a deeper understanding of the emotional experience that the songwriter wants to convey. Thus, diction is a crucial element in the formation of meaning and atmosphere in the lyrics of this song.